GAS CHROMATOGRAPHIC ANALYSIS OF THE CHEMICAL COMPOSITION OF ETHYL ALCOHOL OBTAINED FROM PLANTS OF THE GENUS ASTERACEAE - G.E. Azimbayeva; A.K. Kamysbayeva; Abdigali Bakibaev (Academic Scientific Journal of Chemistry, 2021)
In recent years, serious attention has been paid around the world to the chemical and biotechnological processing of biomass of easily renewable plant raw materials. One of the most mass-produced aliphatic alcohols is ethyl alcohol. The aim of this work was gas chromatographic analysis of the chemical composition of ethyl alcohol obtained from plants of the genus Asteraceae (dahlia and jerusalem artichoke tubers, chicory and big burdock roots) growing on the territory of Kazakhstan. The article discusses the methods of obtaining and application of ethyl alcohol. The results of the analysis of the chemical composition of ethyl alcohol obtained from plants of the genus Asteraceae are presented. As a result of the study, alcohols were obtained in different concentrations. The chemical composition of ethyl alcohol was determined by gas chromatography. The impurity composition of ethyl alcohol obtained from various types of raw materials is also shown. The composition of impurities in various samples of ethanol and alcohol-containing products is considered in detail. The results of the study were discussed, and the peculiarities of using the gas chromatography method were shown